Adult-specific over-expression of the Drosophila genes magu and hebe increases life span and modulates late-age female fecundity - Li, Yishi (2008)
During Drosophila aging mortality rate increases exponentially and progeny production per animal declines dramatically, correlating with decreased number and division of somatic and germ-line stem cells in the gonads. To search for genes that might promote both longevity and fecundity, a P element transposon (PdL), containing an outwardly directed, doxycycline-inducible promoter was used to generate conditional mutations. Mutant females were screened for increased fecundity at late ages in the presence of doxycycline. Two genes were identified, named hebe (CG1623) and magu (CG2264), that when over-expressed in adult flies could increase life span by ~5–30% in both sexes and increase female fecundity at late ages. Transcripts for magu are enriched in the Drosophila stem cell niche region, and magu encodes a protein related to the human SMOC2 regulator of angiogenesis. While moderate over-expression of magu in adult females increased fecundity at late ages, high-level over-expression of magu was maternal-effect lethal. The data demonstrate that adult-specific over-expression of hebe and magu can increase life span and modulate female fecundity, and provide further evidence against obligatory trade-offs between reproduction and longevity.